Hubungan Pola Asuh Orangtua Terhadap Kematangan Emosi Remaja - Basuni, Dita Nan Diya; Rahmawati; Khairun, Deasy Yunika (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
The purpose of this study was to determine the relationship between parental care and adolescent emotional maturity at SMP N 1 Serang City. The population is taken with the condition that adolescents aged 13-15 years from these criteria obtained the number of respondents 158 students through random sampling. The research method used is quantitative. The measuring instrument used is a questionnaire measuring scale consisting of aspects of parenting with a reliability value of 0.941 and a questionnaire measuring scale consisting of aspects of emotional maturity with a reliability value of 0.921. Based on the results of the regression test, the results obtained sig (2-tailed ) is 0.000 < 0.05, and the correlation coefficient (r) is 0.303 (p < 0.01). This means that there is a significant relationship between parenting and adolescent emotional maturity, where the higher the parenting style will have an impact on emotional maturity.